Compreensão e diálogo : contribuições da hermenêutica gadameriana à educação - Cruz, Raimundo José Barros (2009)
The significant success achieved by the hermeneutic within the recent debate of sciences, is due to its critical position about the way of thinking of natural sciences, and the legitimating tendency of a rational, domineering being of possible contexts. Dealing with the pedagogical relations, taking the hermeneutical dialogues as indispensable conditions and mediations to the formation and education process of everybody who is involved with the pedagogical process, sends us, thus, to the critical confrontation of monological structures of a contemporary society which reveals the incapacity for the dialogue. We find in the Hans-George Gadamer pedagogical hermeneutic, the fertile ground to take up this discussion. Convinced that the contemporary society shows a lack of capacity for dialogue, which is associated with the technical and scientific development, this author, criticizes the contemporary society, presenting the dialogical component in opposition to the monological structures related to the instrumental rationalism. Taking the dialogue in its more demanding meaning, shows it as a natural human being attribute, who has a changing strength, which reveals the proper human being. When this discussion is transferred to the sphere of pedagogical relations, we intend to justify a relation based on dialogue and when overcoming a superposition between interlocutors, offer formative processes where everybody, when contributes with its individuality, collaborates with the mutual growth, giving the opportunity to the appearance of new horizons, builders of infinite knowledge